Current situation regarding lead exposure in birds in Japan (2015–2018); lead exposure is still occurring - ISHII, Chihiro (J Vet Med Sci, 2020)
Birds of a number of species have died as a result of lead (Pb) poisoning, including many Steller’s sea eagles (Haliaeetus pelagicus) and white-tailed sea eagles (Haliaeetus albicilla) in Hokkaido, the northernmost island of Japan. To address this issue, the use of any type of Pb ammunition for hunting of large animals was prohibited in Hokkaido in 2004. However, Pb poisoning is still being reported in this area, and there are few regulations regarding the use of Pb ammunition in other parts of Japan, where it has been reported that eagles and water birds have been exposed to Pb. This study was performed to accurately determine the current level of Pb exposure of birds found dead in the field or dead in the wild bird centers in Japan (June 2015–May 2018) and to identify the sources of Pb. Pb exposure was found to still be occurring in raptors and water birds in various parts of Japan. Twenty-six point five % and 5.9% of the recorded deaths of Steller’s sea eagles and white-tailed sea eagles, respectively, were found to have been poisoned by Pb. In addition, Pb isotope ratio analysis showed that both Pb rifle bullets and Pb shot pellets cause Pb exposure in birds, and these endangered eagles are also exposed to Pb in Hokkaido due to the illegal use of Pb ammunition. Changing to Pb-free ammunition, such as copper (Cu) rifle bullets, steel shot pellets, or bismuth shot pellets, will be essential for the conservation of avian species in Japan.